Mechanical lower back pain and sacroiliac joint dysfunction in golfers at two golf clubs in Durban, South Africa - Siyabonga H. Kunene; Hlengiwe Luthuli; Mthandeni Nkosi; Maqsood Haffejee; Iftikaar Jooma; Scott Munro (AOSIS, 2018)
Background: Mechanical lower back pain (MLBP) and sacroiliac joint dysfunction (SIJD) are common problems among golfers. There are currently few studies on golfers regarding the relationship between MLBP and SIJD. Objective: The objective of this study was to determine the prevalence of MLBP and SIJD and their association in golfers at two golf clubs in Durban, South Africa. Method: A correlation design included convenience sampling. The Standardised Nordic Questionnaire for the analysis of musculoskeletal symptoms determined the prevalence of MLBP. Sacroiliac joint pain provocative tests determined the prevalence of SIJD. Institutional ethical clearance was granted and consent from participants was obtained. Data were collected over 3 weeks and SPSS was used to calculate descriptive and inferential statistics. Results: There were 271 participants dominated by males (86.7%) aged between 39 and 47 years (33.2%). A total of 123 (45%) of the participants presented with MLBP and 62 (23%) with SIJD. The MLBP prevalence was moderately associated with age (χ2 = 71.22, p = 0.004) and years of experience (χ2 = 69.93, p = 0.001). The SIJD prevalence was moderately associated with age (χ2 = 55.49, p = 0.003) and poorly associated with years of experience (χ2 = 44.93, p = 0.005). Twenty-two per cent (60) had both MLBP and SIJD and 54% (146) had neither. A strong association (χ2 = 88.234, p = 0.000) between MLBP and SIJD was observed. Conclusion: There was a high prevalence of MLBP and SIJD and a strong association between them. A comprehensive management approach is recommended for golfers with MLBP and SIJD. Clinical Implications: This study will provide valuable knowledge that will assist clinicians, especially physiotherapists, in their clinical management of golfers with MLBP and SIJD. Intervention studies are needed to address lower back and sacroiliac joint problems reported in this study.